The role of macrophages phenotypes in the activation of resolution pathways within human granulosa cells - Thaise S. Martins; Bruno M. Fonseca; Irene Rebelo (BMC, 2022)
Abstract Background Inflammatory state within the ovaries can disrupt normal follicular dynamics, leading to reduced oocyte quality and infertility. How the production of inflammatory mediators generated by macrophages with different gene expression profile (M1 and M2) might activate inflammatory pathways, such as cyclooxygenase-2 (COX-2) and 5-, 12-, and 15-lipoxygenase (LOX), in human granulosa cells (hGCs) remains unclear. Methods In this study, we evaluated how M1 and M2 macrophages found in the ovaries affect the functions of hGCs isolated from women undergoing assisted reproductive technology (ART) and human ovarian granulosa COV434 cells. For this purpose, a model of interaction between hGCs and COV434 cells and conditioned media (CMs) obtained from culture of M0, M1 and M2 macrophages was established. We used real-time PCR and western blotting to detect the expression of COX-2 and 5-, 12-, and 15-LOX as biomarkers of oocyte competence. Results Our data showed that M2 macrophages with anti-inflammatory characteristics were able to significantly increase the expression of COX-2 in hGCs. We also demonstrated that M1 macrophages with pro-inflammatory characteristics were able to significantly increase the expression of 12-LOX in hGCs. However, there was no observed expression of 5-LOX and no significant alteration in the expression of 15-LOX in hGCs. Regarding COV434 cells, we found that CM from M2 macrophage resulted in an increase in COX-2, 5-LOX and 15-LOX mRNA and protein levels. No expression of 12-LOX by COV434 cells was observed when exposed to CMs from M1 and M2 macrophages. Conclusions Our research indicated that the production of pro-resolving mediators by hGCs can, at least in part, reverse the physiological inflammation present in the ovaries.